Analisis Keterampilan Menutup Pembelajaran pada Mahasiswa saat Ujian Microteaching - Nonny Rulisty Putri Sutikno; Namira Choirani Fajri (Jurnal Bima : Pusat Publikasi Ilmu Pendidikan Bahasa dan Sastra, 2026)
Closure skill is one of the essential basic teaching skills that prospective teachers must master, yet it often receives less attention compared to the skill of opening a lesson. This study aims to describe the implementation of students' closure skills in micro teaching practice, identify the obstacles encountered, and analyze the factors influencing them. This study employed a descriptive qualitative approach with four sixth-semester students at STKIP PGRI Situbondo who were undergoing a micro teaching practice examination as subjects. Data were collected through observation and documentation in the form of video recordings, then analyzed using the Miles and Huberman model of data reduction, data display, and conclusion drawing. The results show that all four students were able to close the lesson formally, each displaying a distinct personal style, ranging from a brief formal closing, a personal apology, to inviting students to pray together. However, none of the four students carried out three substantive components of closure skill, namely reflecting on and summarizing the material, actively evaluating students' understanding, and providing follow-up. These findings indicate a gap between the fulfillment of the formal form and the substantive function of lesson closure, which is presumed to be influenced by performance pressure within the examination context. This study implies that strengthening students' closure skills should focus on the substantive aspects rather than merely the formal stages, in order to improve the effectiveness of prospective teachers' instructional practices in the future.